ANALISIS PEMANFAATAN TEKNOLOGI INFORMASI DALAM MANAJEMEN RESIKO BENCANA BANJIR DI KECAMATAN BARUGA - Intan Anuggrah Yuandi (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
Vigilance system about flood not currently able to work with automatic and real-time to determine the height of the water level of the river. This causes around the average citizen does not know when the surface of the river would overflow. In this study designed information system that works automatically by means knowing height the water. This system design by implementing an ultrasonic sensor based Arduino Uno ATMega32 who calculating high of water, SMS Gateway as media for distributing information about high of the water and web mapping based GIS. Test result can be conluding that the system is able to work with the response realtime for reading accuracy to 100%, averaged of delay for sending SMS from system 15 second, averaged time of sending SMS 8,8 seond and delay of reading sensor to reading mapping 10 second because there was time waiting for sending data from GSM module to GSM modem.